Information and Communication Technologies (ICTs) and International Negotiations in a Non-Profit Organization, Lima – Peru - Jhaquelin M. MENDOZA CASTAÑEDA; Saraí N. SAMÁN CHINGAY; Marcelo C. LUDEÑA PALACIOS; Miguel A. ROJAS LARA (Communications of International Proceedings, 2024)
The development and application of ICTs are becoming relevant in the human being; its diffusion has been extended in business organizational sectors that seek to increase new alternatives and ideas of high impact in the international business activity. The objective of this research is to determine the relationship between ICT and International Negotiations in a non-profit organization, Lima. For which reason, the study has been conducted with non-experimental quantitative transversal approach, with a descriptive correlational style. The instrument applied was the questionnaire, asked to a finite population of 30 direct collaborators in relation to the variables in a non-profit organization, Lima, Peru. As a result, there is a perfect positive significant relation was obtained with a value of 0.985 and a significance level of 0.000 being less than 0.05. In such a way it is demonstrated that the variables ICT and international negotiations in a non-profit organization – Lima, has a direct relation. Therefore, the better interaction and application of ICT, the greater efficiency in international negotiations. To conclude, ICT is effective in a non-profit organization Lima. It is estimated and recommended that organizations must implement this tool to facilitate decision making. In the same way, it can generate greater results in terms of efficiency, dynamics, and effectiveness on international negotiations.
Keywords: ICT; international negotiations; ICT training.